EMPLOYEE EMPOWERMENT AND ACHIEVEMENT MOTIVATION ON THE PERFORMANCE OF MADRASAH TEACHER ALIYAH PRIVATE DARUL ARAFAH DELI SERDANG - Handoko, Handoko; Akso, Maimun (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
Therefore, attention to the improvement of teacher performance becomes important and becomes a necessity. Especially with the various developments of science and technology today, then a teacher is required to be able to adapt himself so that knowledge and skills given to students are not left behind by the development of science itself. Â Â Â Â Â  The study aimed to find out: (1) the relationship between the empowerment of subject teachers and teacher performance,Â  Â (2) Â the relationship between achievement motivation and the performance of teacher teachers, and (3) the relationship between empowerment of teacher meetings. The population of this research is all teachers of Madrasah Aliyah Swasta Darul Arafah Deli Serdang are 54 people. Â The entire population is used as the research sample. The test requirement is done to test normality, linearity, and independence among independent variables. The data analysis technique used correlation and regression and simple correlation and regression and multiple correlation at significance level ï¡ = 0,05.